An integrative approach to investigate the textural properties and possible mechanisms in the formation of woody breast in broilers - Welter, Amelia (Kansas State University, 2021)
Woody breast (WB) is a myopathy observed in chicken breast meat (Pectoralis major), that is characterized by a tough and rubbery texture. The objective of this study was to investigate factors and enzymatic activities contributing to the abnormal texture seen in WB and utilize integrative omics (proteomics/lipidomics) to examine the functionality/integrity of WB sarcoplasmic reticulum (SR). Fourteen Ross line broiler breast fillets (7 severe WB and 7 normal) were collected at 3 h postmortem from a commercial processing plant. Around 8 h postmortem, each sample was trimmed, weighed, vacuum packaged and frozen at -20°C. A section of the cranial end of each fillet was pulverized in liquid nitrogen to measure pH, objective tenderness, sarcomere length, free calcium concentration, proteolysis, calpain activity, collagenase activity, collagen content, collagen crosslinks and peak transitional temperature measurements. The SR fractions of the samples were extracted via ultracentrifugation through discontinuous sucrose gradients. The SR factions were separated into lipid and protein for lipidomic and proteomic analysis. The WB fillets were heavier than normal chicken breast fillets (522.9 vs. 446.9g; P<0.05) and exhibited a higher pH (6.17 vs. 5.83; P<0.05). Objective tenderness was not significantly different (34.09 vs. 37.69 N; P>0.10), but WB samples tended to have shorter sarcomeres (1.70 vs. 2.02 µm; P=0.05) and less intact troponin-T compared to normal breast samples (relative intact troponin-T band density: 49.98 vs. 56.97%; P=0.05) at 8 hrs postmortem. For enzymatic activity, WB had more autolyzed μ/m calpain levels (71.05 vs. 59.12% calpain autolyzed; P<0.01) and more activated collagenase (13.24 vs. 7.84% activated MMP2; P<0.05). In addition, the purge from WB samples also had higher levels of free calcium compared to normal samples (6.2 vs. 4.2 nmol calcium/mg protein; P<0.05). There was increased collagen levles present in the WB samples compared to normal chicken breast samples (3.89 vs. 2.08 mg collagen/g muscle tissue; P<0.05), as well as more mature crosslinks in WB (0.23 vs. 0.14 mol PYD/mol collagen; P < 0.05; 0.07 vs. 0.04 mol DPD/mol collagen; P < 0.01). Finally, WB had a higher peak transitional temperature compared to N (65.47 vs. 63.72°C; P<0.05). Lipidomics data revealed significant differences for 66 phospholipid species and WB SR had a less relative % of phosphatidylcholine (PC) and more phosphatidylethanolamine (PE), phosphatidylserine (PS) and lysophosphatidylcholine (LPC) (P<0.05). Proteomics data revealed 677 proteins with differential abundance with WB SR having an upregulation of calcium transport proteins (ex. sarcoplasmic/endoplasmic reticulum calcium ATPase), a downregulation of proteins responsible for calcium release and signaling (ex. ryanodine receptors), and no difference for calcium storage proteins (ex. Calsequestrin). There was a significant upregulation to stress response proteins in WB (P<0.05). As for membrane integrity, there was an upregulation of phospholipase A2 (PLA2) in WB SR (P<0.01) and membrane repair proteins (P<0.05). Interestingly, cholinesterase exhibited a 7.62-fold increase in WB SR (P<0.01). This study showed that the cause of texture abnormality of WB may be the combined effects of increased collagen and more calcium being released from the SR early postmortem. The elevated free calcium levels in WB meat may be due to alterations in lipid structure and increases in the breakdown of SR membrane phospholipids ultimately causing integrity issues. On the other hand, the upregulation of cholinesterase activity is an indicator of the presence of cholinesterase inhibitors. Perhaps, the action potential in WB is prolonged due to the inhibition of cholinesterase causing the additional release of calcium from the SR.
Keywords: Poultry; Woody breast; Calcium; Sarcoplasmic reticulum; Lipidomics; Proteomics